Analisis Resiliensi Psikologis dan Motivasi Berprestasi Atlet Bulutangkis - Nurin Nufus Zakiyah; Soedjatmiko Soedjatmiko; Indra Ramadhan (Prodi Pendidikan Jasmani dan Olahraga, 2026)
The purpose of the study is analyze the level of psychological resilience and achievement motivation of badminton athletes. The research uses a quantitative descriptive method with a population of 30 PB Pendowo athletes. The sampling technique was purposive sampling based on specific criteria, resulting in 15 athletes being selected as the research sample. The research instrument for measuring resilience is the Connor Davidson Resilience Scale (CD-RISC) with a validity value of 0,46 to 0,68 and a reliability value of 0,87, and to measure motivation Sport Motivation Scale (SMS-II) with validity values ranging from 0,455 to 0,911 and a reliability value of 0,946. The research result for the resilience variable shows that 2 athletes (13%) are in the high category, 12 athletes (80%) are in the medium category, and 1 athlete (7%) is in the low category. For the achievement motivation result, 3 athletes (20%) fell into the high category, 10 athletes (67%) into the medium category, and 2 athletes (13%) into the low category. In conclusion, the results indicate that PB Pendowo athletes in the 13-16 age group have medium psychological resilience and achievement motivation. Further research is suggested to use a larger and more proportional sample in each age group.